Functions of the Essential Gene mraY in Cellular Morphogenesis and Development of the Filamentous Cyanobacterium Anabaena PCC 7120 - Liu, Jing; Xing, Wei-Yue; Zhang, Ju-Yuan; Zeng, Xiaoli; Yang, Yiling; Zhang, Cheng-Cai (Frontiers in Microbiology, 2021)
Bacterial cell shape is determined by the peptidoglycan (PG) layer. The cyanobacterium Anabaena sp. PCC 7120 (Anabaena) is a filamentous strain with ovoid-shaped cells connected together with incomplete cell constriction. When deprived of combined nitrogen in the growth medium, about 5-10% of the cells differentiate into heterocysts, cells devoted to nitrogen fixation. It has been shown that PG synthesis is modulated during heterocyst development and some penicillin-binding proteins (PBPs) participating in PG synthesis are required for heterocyst morphogenesis or functioning. Anabaena has multiple PBPs with functional redundancy. In this study, in order to examine the function of PG synthesis and its relationship with heterocyst development, we created a conditional mutant of mraY, a gene necessary for the synthesis of the PG precursor, lipid I. We show that mraY is required for cell and filament integrity. Furthermore, when mraY expression was being limited, persistent septal PG synthetic activity was observed, resulting in increase in cell width. Under non-permissive conditions, filaments and cells were rapidly lysed, and no sign of heterocyst development within the time window allowed was detected after nitrogen starvation. When mraY expression was being limited, a high percentage of heterocyst doublets were found. These doublets are formed likely as a consequence of delayed cell division and persistent septal PG synthesis. MraY interacts with components of both the elongasome and the divisome, in particular those directly involved in PG synthesis, including HetF, which is required for both cell division and heterocyst formation.